Computer-based operational and decision support for surgical services. (1st January 2000) - Spangler, William E.; Strum, David P.; May, Luis G. Vargas and Jerrold H.
In the face of increasing demands for services and tighter constraints on resources, medical centres are searching for ways to improve efficiencies and reduce costs. This paper describes the design and development of a system, called Resource Coordination for Surgical Services (RCSS), that is intended to help managers improve overall utilisation of surgical suites.